Memorandum of understanding between Universiti Teknologi MARA and DNEX RFID Sdn Bhd (DRSB) / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2019)
UiTM and DRSB will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.